The Effect of Toddler Growth Assessment Training Videos on Improving Knowledge of Posyandu Cadres - Maliha Amin; Elita Vasra; Rita Rukmawati; Intan Kumalasari (MBUnivPress, 2022)
Posyandu cadres are at the forefront of implementing growth monitoring programs for children under five, the results of growth monitoring by cadres will be included in the integrated health center reporting which will then become the basis for policies for local and central governments in solving nutritional problems. The results of previous studies showed that many cadres had less knowledge about assessing the growth of children under five. Video media is one of the effective learning media that can increase knowledge because in the process it involves all the five senses, it is easier to understand and interesting. This study used a quasi-experimental method with a one-group pre-test post-test design. The sample size was selected using a total sampling technique, namely 76 posyandu cadres at Dempo Health Center. Collecting data using an instrument in the form of a questionnaire related to the assessment of toddler growth.The results of the Marginal Homogeneity statistical test obtained a p-value of 0.000 (p-value <0.05) so it was concluded that the intervention with video training on toddler growth was effective in increasing the knowledge of cadres.